The properties of silica nanoparticles modified with cationic surfactant - Bryleva, E.Yu.; Vodolazkaya, N.A.; Mchedlov-Petrossyan, N.O.; Samokhina, L.V.; Matveevskaya, N.A. (Functional Materials, 2006)
The properties of SiO₂ nanoparticles interface modified with cationic surfactant molecules has been studied. Using a fluorescent indicator 2,7-dichlorofluorescein as the surface probe, it has been demonstrated that a bilayer is formed on the SiO₂ surface providing similarity of the nanoparticle surface in aquous media with that of surfactant micelles.